2019
DOI: 10.1007/s00335-019-09795-3
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and preliminary validation of the molecular mechanism of fat deposition in fatty and lean pigs by high-throughput sequencing

Abstract: Fat deposition in muscle includes intramuscular fat (IMF) and intermuscular fat. IMF content is an index of pork quality; however, because IMF content is difficult to measure in vivo in young animals, conventional breeding for IMF content is difficult to carry out. The mechanism and progression of animal fat deposition is not well understood, and there are currently no effective control methods. In this study, using Laiwu and large white pigs as the research subjects and RNA sequencing technology, we analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 36 publications
0
18
0
1
Order By: Relevance
“…The Laiwu pig is an excellent breed raised in China with a high IMF content. Several previous studies concerning IMF content have been reported; however, most of these studies were performed to compare the difference between two breeds of pigs [14,20,21] to investigate DEGs associated with IMF deposition. However, in animal production, we found that IMF content varies vastly among individual Laiwu pigs.…”
Section: Discussionmentioning
confidence: 99%
“…The Laiwu pig is an excellent breed raised in China with a high IMF content. Several previous studies concerning IMF content have been reported; however, most of these studies were performed to compare the difference between two breeds of pigs [14,20,21] to investigate DEGs associated with IMF deposition. However, in animal production, we found that IMF content varies vastly among individual Laiwu pigs.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to studies on lncRNAs in cattle, there are also numerous high-throughput sequencing studies comparing different pig species. For example, researchers found DEGs between Jinhua and Landrace pigs [73] and Laiwu and Large White pigs [74] . Although these studies have identified differentially expressed candidate lncRNAs related to adipose tissue accumulation, there are still some drawbacks.…”
Section: Pigsmentioning
confidence: 99%
“…Regarding mammalian adipose tissue transcriptomes, fatty acid synthesis in pigs has been described compared to other tissues [67][68][69]. Studies of intramuscular fat (IMF) in pigs have identified potential genes and signaling pathways, such as AMP-activated protein kinase (AMPK), which plays a critical role in controlling lipid metabolism [70,71] and incRNA expression of IMF deposition [68]. In cattle, global transcriptomes in adipogenesis have given insights into the regulation of bovine adipogenic differentiation [72].…”
Section: Transcriptomicsmentioning
confidence: 99%